Proces pokojowy w Irlandii Północnej w latach 90-tych i perspektywy uregulowania konfliktu - Wróbel, Marzena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
At the beginning the paper presents a brief historic outline of the conflict. It describes the strife of the two communities of Northern Ireland that date back to the division of the island in 1921. It also reminds the sources of the conflict that originated with the English conquest of the Celtic Ireland of 13th century. Next, the author analyzes the stages of the peace process in the ‘90s of 20th century, including the elections to the local Assembly of November 2003. In conclusions the author observes that the biggest problem is the popularity of extremist political platforms in the society. This conclusion is not entirely pessimistic, though. The author hopes that the community of Ulster and its political representatives have become so fatigued with the decades of strife that they may finally choose peace this time.